БЎЛАЖАК ЎҚИТУВЧИЛАРНИНГ ЎҚУВ – БИЛИШ ФАОЛИЯТИНИ РИВОЖЛАНТИРИШДА ИНТЕРФАОЛ МЕТОДЛАР - Пазылова, М.Е. (SCIENCE and SOCIETY, 2021)
In this article, the pedagogical teachings created by our thinker-ancestors will give future teachers the opportunity to develop their professional skills and develop their educational and cognitive activities, and the learning movement can provide effective and professional training for future teachers.